Pengaruh Pengantar Akuntansi, Literasi Digital, Dan Self-Regulated Learning Terhadap Keberhasilan Pembelajaran Akuntansi Keuangan Berbasis Daring - Pirmina Setyowati; Rochmawati Rochmawati (Jurnal Pendidikan Akuntansi (JPAK), 2021)
This research to analyze whether there is an influence between the introduction of accounting, digital literacy and self-regulated learning on the success of online-based financial accounting learning in accounting education students of class 2018. This research is quantitative by taking the data through questionnaires. Based on the results of the regression analysis, it can be seen that in the partial test (t test) the three variables, namely X1, X2 and X3, have t value greater than t table. These results conclude that the three variables have a positive effect on the success of online-based financial accounting learning or it can be said that Ho is rejected and Ha is accepted. The results of the f-test indicate that Ho is rejected and Ha which states that there is a positive influence between the introduction of accounting, digital literacy and self-regulated learning simultaneously on the success of online-based financial accounting learning. In this study, the resulting determinant coefficient is that all independent variables have an effect on the dependent.